The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1212/01.wnl.0000128134.84230.9f
|View full text |Cite
|
Sign up to set email alerts
|

Low thyroid-stimulating hormone as an independent risk factor for Alzheimer disease

Abstract: Lowered TSH within the normal range is a risk factor for AD, independent of several cerebrovascular risk factors and confounding variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(81 citation statements)
references
References 33 publications
2
72
0
1
Order By: Relevance
“…However, we demonstrate that elderly subjects with cognitive impairment have lower T3, T4 and TSH hormone levels, and higher systolic BP, compared to elderly healthy subjects. This result was in agreement with van Osch et al, who reported that Alzheimer's disease patients had significantly lower levels of TSH [26]. Lower levels of TSH were associated with a more than two-fold increased risk of Alzheimer's disease, independently of other risk factors.…”
Section: Discussionsupporting
confidence: 92%
“…However, we demonstrate that elderly subjects with cognitive impairment have lower T3, T4 and TSH hormone levels, and higher systolic BP, compared to elderly healthy subjects. This result was in agreement with van Osch et al, who reported that Alzheimer's disease patients had significantly lower levels of TSH [26]. Lower levels of TSH were associated with a more than two-fold increased risk of Alzheimer's disease, independently of other risk factors.…”
Section: Discussionsupporting
confidence: 92%
“…There are conflicting data on the risk of dementia in elderly patients with SHyper, and the mechanism is unclarified [54,55,56,57,58]. A recent systematic review provided evidence for an association between SHyper or low serum TSH within the reference range and cognitive impairment or dementia [59].…”
Section: Risks Associated With Persistent and Untreated Endo Subclinimentioning
confidence: 99%
“…Subclinical as well as clinical thyroid diseases are shown to be connected with cardiovascular disease and vascular risk factors with accumulating epidemiologic evidence that vascular risk factors increase the risk of AD, indicating a connection between thyroid function and AD [9,[11][12][13][14] . It could be that T4 may generate oxidative stress and damage neurons [15] .…”
mentioning
confidence: 99%